Revitalisasi UMKM Pengrajin Kayu Kota Medan untuk Penguatan Daya Saing melalui Optimalisasi Peralatan Produksi dan Efektivitas Biaya Produksi - Nurhaflah Soraya; Rahmadani, Rahmadani; Khairi Anshor; Devanta Abraham Tarigan; Rika Githamala Ginting (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
This community service program aims to enhance the competitiveness of woodcraft SMEs in Medan City through revitalization strategies focused on optimizing production equipment and improving cost-effectiveness. The main challenges faced by these SMEs are outdated technology, inefficient tools, and high operational costs, which result in low productivity and suboptimal product quality. Through technical training, mentoring, and the implementation of equipment improvement as well as cost management practices, the program successfully increased production efficiency, reduced unnecessary expenses, and improved the quality of wooden products to become more competitive in local and regional markets. The results indicate significant improvements in production capacity, cost efficiency, and entrepreneurial knowledge in sustainable business management, thereby strengthening the competitiveness of woodcraft SMEs amid an increasingly dynamic market environment.